Why Teachers Assign Socially Unequal Marks. A Case for Establishing Tertiary Origin Effects in the Model of Primary and Secondary Effects of Educational Research - Marcel Helbig; Tatiana Morar (International Journal of Learning, Teaching and Educational Research, 2018)
Subjective expected utility theory assumes that educational paths result from the interplay of primary effects – students' cognitive skills – and secondary effects – academic decisions regarding their educational future. We argue that thus far, the assignment of marks has not been accounted for in the scope of Boudon's model of primary and secondary effects. We propose an elaborated model in which psychological traits are included in the concept of primary effects and introduce a further component, tertiary effects, indicating teachers' socially unequal assignment of marks. Empirically, we demonstrate that a specific psychological skill set has moderate influence on students' marks, it does not, however, account for social inequalities in the assignment of marks. Nevertheless, our findings show that social differences in marks can almost entirely be explained by cognitive, psychological and resource-related tertiary effects. Furthermore, there is some evidence that the extent of tertiary effects is associated with the scholastic configuration of educational institutions. Lastly, we observe that teachers unknowingly overvalue children from higher social classes because they deem them more talented, more willing to achieve and better equipped with parental resources than children from lower social classes. A key question for future research is to find reasons for this biased perception.
Keywords: 330; social inequality; school mark; primary; secondary and tertiary effects; teacher bias; Germany